2019
DOI: 10.1002/asi.24315
|View full text |Cite
|
Sign up to set email alerts
|

Academic collaboration rates and citation associations vary substantially between countries and fields

Abstract: Research collaboration is promoted by governments and research funders but if the relative prevalence and merits of collaboration vary internationally different national and disciplinary strategies may be needed to promote it. This study compares the team size and field normalised citation impact of research across all 27 Scopus broad fields in the ten countries with the most journal articles indexed in Scopus 2008-2012. The results show that team size varies substantially by discipline and country, with Japan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 50 publications
3
22
1
2
Order By: Relevance
“…The coefficients of Authors , Instit are positively signed. This agrees with existing studies ( Bornmann, 2017 ; Card and DellaVigna, 2017 ; Ronda-Pupo and Katz, 2017 ; Struck et al., 2018 ; Thelwall and Maflahi, 2019 ). The sign, however, diverges with the findings of others ( Maz-Machado and Jimenez-Fanjul, 2018 ; Wongkhae et al., 2017 ).…”
Section: Resultssupporting
confidence: 94%
See 3 more Smart Citations
“…The coefficients of Authors , Instit are positively signed. This agrees with existing studies ( Bornmann, 2017 ; Card and DellaVigna, 2017 ; Ronda-Pupo and Katz, 2017 ; Struck et al., 2018 ; Thelwall and Maflahi, 2019 ). The sign, however, diverges with the findings of others ( Maz-Machado and Jimenez-Fanjul, 2018 ; Wongkhae et al., 2017 ).…”
Section: Resultssupporting
confidence: 94%
“…Bornmann 2017, Ronda-Pupo and Katz (2017), Struck et al (2018) and Thelwall and Maflahi (2019) found statistically significant positive effects of author collaborations on citation counts in Web of Science (WOS) and Scopus databases across disciplines over the period 1976 and 2012. The modelling included Ordinary Least Squares (OLS), negative binomial and zero-inflated Poisson regressions.…”
Section: Empirical Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…As to whether more collaborative scholars are more productive, the evidence is mixed, especially when using fractional counting (Abramo et al 2017), and collaboration rates differ significantly across countries and disciplines (Thelwall and Maflahi 2019;Fox et al 2017). In general, more productive scientists tend to collaborate more with international colleagues, and the most productive or top performers are much more internationalized than their lower-performing colleagues (Kwiek 2019: 23-71).…”
Section: International Research Collaboration and Research Productivitymentioning
confidence: 99%